Analysis of RAG expression by peripheral blood CD5+ and CD5− B cells of patients with childhood systemic lupus erythematosus. Issue 4 (26th August 2005) - Morbach, H; Singh, S K; Faber, C; Lipsky, P E; Girschick, H J
Abstract : Background: The assembly of immunoglobulin genes during B cell development in the bone marrow is dependent on the expression of recombination activating genes (RAG) 1 and 2. Recently, RAG expression in peripheral blood IgD+ B cells outside the bone marrow has been demonstrated and is associated with the development of autoimmune diseases. Objective: To investigate RAG expression in the CD5+ or CD5− IgD+ B cell compartment in childhood systemic lupus erythematosus (SLE). Methods: Using a combination of flow cytometric cell sorting and reverse transcriptase polymerase chain reaction analysis of cDNA libraries generated from individual cells, the expression of RAG, VpreB, and CD154 mRNA by individual peripheral blood B cells of three paediatric SLE patients was examined in detail. Results: While only one patient had a significantly increased frequency of RAG+ B cells in the CD5− B cell population, all patients showed higher frequencies of RAG+ B cells in the CD5+IgD+ B cell population. The frequency of RAG+ IgD+CD5+/− B cells was reduced during intravenous cyclophosphamide treatment. In healthy age matched children, RAG expressing IgD+ B cells were hardly detectable. Coexpression of RAG and VpreB or CD154 mRNA could only be found in SLE B cells. Conclusions: RAG expression in peripheral blood B cells of SLE patients is particularly increased in the IgD+CD5+ B cell population. CD5+ and CD5− B cells in SLE have the potential to undergo receptor revision leading to the generation of high affinity pathogenic autoantibodies.